Epidendrum schistochilum - Karremans Lok, Adam Philip (2018)
Epidendrum schistochilum is recognized by the large, erect plants, distichous leaves, numerous, successive, non-resupinate flowers. The flowers are snow white with a thick, triangular, three-lobed, orange callus in the middle of the three-lobed, fimbriate lip.